Characteristic pattern of species diversity on the Canary Islands - Steinbauer, Manuel Jonas; Beierkuhnlein, Carl (ERDKUNDE, 2010)
We use an island specific presence/absence data set for the Canary Islands' Arthropoda, Spermatophyta, Fungi, Lichenes, Bryophyta, Mollusca, Chordata, Pteridophyta, Annelida and Nematoda to assess the relative influence of environmental and historical factors on species distribution and endemism. Species richness and the percentage of island endemic species as well as similarity indices for island comparisons were calculated for all species groups. Hierarchical partitioning is used to identify the independent and joined influence of 21 environmental and historical variables. The pattern of species richness is best explained by island elevation. Elevation reflects a variety of factors that contribute to habitat diversity. A similar pattern is detected for the percentage of single island endemics (pSIE), a factor associated with speciation. Variables associated with geographical distance have highest explanatory power for biotical similarity of islands. Various Canary Islands species groups show strong distance-decay within the archipelago. According to our findings, speciation is not necessarily driven by species richness or island age alone. Thus, we conclude that correlations between species richness and pSIE, identified in previous studies, could represent an artefact related to differing degrees of isolation between zonal altitudinal ecosystems. This would lead to an increase of speciation with altitude resulting in higher values for pSIE on high altitude islands.